Kompetence ve veřejné správě a možnosti sledování efektivnosti vložených prostředků k ochraně životního prostředí - Obršálová, Ilona; Kukeňová, Pavla (Univerzita Pardubice, 2002)
One of the most important tasks of public administration is efficiency of public expenditures control. The contribution analyses information for decisions in the district and focuses on one of environmental compartment - soil. Indicators for efficiency assessment are presented in both monetary and natural expresion.
Keywords: environmentální náklady; Efektivnost; ochrana životního prostředí; veřejná správa